2002
DOI: 10.1016/s0735-1097(02)02160-5
|View full text |Cite
|
Sign up to set email alerts
|

Absolute concentrations of high-energy phosphate metabolites in normal, hypertrophied, and failing human myocardium measured noninvasively with 31P-SLOOP magnetic resonance spectroscopy

Abstract: In human heart failure due to DCM, both PCr and ATP are significantly reduced. Ratios of PCr to ATP underestimate changes of high-energy phosphate levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
233
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(250 citation statements)
references
References 38 publications
10
233
0
7
Order By: Relevance
“…If indeed, higher energy consumption and, thus, ATP hydrolysis occurs in failing myocardium, but with an insufficient compensatory increase of NADH production by the TCA cycle, this may explain the pronounced oxidation of the NADH-pool in failing hearts [4], which may eventually result in a mismatch between ATP supply and demand. It has been suggested that such a mismatch precedes the reduction in the total cellular levels of PCr in patients with heart failure [11,99,188].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If indeed, higher energy consumption and, thus, ATP hydrolysis occurs in failing myocardium, but with an insufficient compensatory increase of NADH production by the TCA cycle, this may explain the pronounced oxidation of the NADH-pool in failing hearts [4], which may eventually result in a mismatch between ATP supply and demand. It has been suggested that such a mismatch precedes the reduction in the total cellular levels of PCr in patients with heart failure [11,99,188].…”
Section: Discussionmentioning
confidence: 99%
“…The total cellular levels of PCr, but also NAD and adenine nucleotides, are reduced in patients with heart failure [11,99,188]. Such changes already occur at the stage of cardiac hypertrophy [99].…”
Section: Pathophysiological Aspects Defects In Ec Coupling In Chronicmentioning
confidence: 99%
“…46 A number of studies have shown decreased phosphocreatine and ATP levels in failing myocardium of both animals and humans. 23,[47][48][49] Myocardial ATP content can decrease by 30%-40% in the failing heart relative to the normal heart. It has been proposed that the failing heart switches from primarily using fatty acids as energy substrates to primarily using glucose for energy production.…”
Section: Cardiac Metabolism In Left Heart Failurementioning
confidence: 99%
“…This technique facilitates in vivo exploration of intracellular metabolism. A low phosphocreatine-to-ATP ratio (PCr/ ATP), indicating a cardiac energy deficit, has been shown in the failing human heart (Beer et al 2002;Conway et al 1991;Hardy et al 1991;Neubauer et al 1997;Neubauer et al 1992). This ratio is correlated with clinical symptoms (Conway et al 1998) and predicts mortality better than the left ventricular ejection fraction (Neubauer et al 1997).…”
Section: Introductionmentioning
confidence: 99%